The sense of early modern writing : Rhetoric, poetics, aesthetics - Robson, Mark, 1968- (Book collections on Project MUSE., 2018)
In The Sense of Early Modern Writing, Mark Robson pursues the relation between the concept of the 'early modern' and modernity, tracing the complex interactions of post-Romantic, philosophical aesthetics and early modern rhetoric and poetics. The book therefore questions the status of what we now think of as literary texts in a period prior to the emergence of literature as a category.